2022
DOI: 10.3389/fendo.2022.1056871
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and central precocious puberty

Abstract: Childhood obesity is a major public health problem worldwide, and the relationship between obesity and central precocious puberty has long been confirmed, however, the mechanisms underlying this association remain elusive. This review provides an overview of the recent progress regarding how childhood obesity impacts on hypothalamic-pituitary-gonadal axis and pubertal onset, focusing on adipokines (leptin and ghrelin), hormone (insulin), and lipid (ceramide), as well as critical signaling pathways (AMPK/SIRT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 75 publications
1
31
0
3
Order By: Relevance
“…In addition, obesity may constitute a chronic stressor and in turn impair brain functions involved in affective control, by inducing chronic inflammation, dysfunctions in the hypothalamic-pituitaryadrenal axis [31], and dysregulations of adipokines [33]. In line with previous findings [25,34], our study also found that girls with the trajectory of increasing adiposity had earlier menarche ages and menarche age was associated with BMI/WHtR trajectories, which may suggest a risk of the metabolic-reproductive interplay among female adolescents with early menarche ages involving adipokines (leptin and ghrelin), hormones (insulin), and lipid, as well as critical signaling pathways (AMPK/SIRT, mTOR) that may integrate the peripheral metabolism and central circuits [35]. Furthermore, the associations between the "rapidly increasing" BMI z score/WHtR trajectory and subsequent neurobehavioral deficits remained significant when taking pubertal timing into consideration (additionally adjusting for menarche age in girls), indicating that rapidly increasing adiposity or abdominal obesity from ages 11 to 15 years may be an independent risk factor for neurobehavioral deficits among female adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, obesity may constitute a chronic stressor and in turn impair brain functions involved in affective control, by inducing chronic inflammation, dysfunctions in the hypothalamic-pituitaryadrenal axis [31], and dysregulations of adipokines [33]. In line with previous findings [25,34], our study also found that girls with the trajectory of increasing adiposity had earlier menarche ages and menarche age was associated with BMI/WHtR trajectories, which may suggest a risk of the metabolic-reproductive interplay among female adolescents with early menarche ages involving adipokines (leptin and ghrelin), hormones (insulin), and lipid, as well as critical signaling pathways (AMPK/SIRT, mTOR) that may integrate the peripheral metabolism and central circuits [35]. Furthermore, the associations between the "rapidly increasing" BMI z score/WHtR trajectory and subsequent neurobehavioral deficits remained significant when taking pubertal timing into consideration (additionally adjusting for menarche age in girls), indicating that rapidly increasing adiposity or abdominal obesity from ages 11 to 15 years may be an independent risk factor for neurobehavioral deficits among female adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…Childhood obesity makes inroads on up to 107.7 million children worldwide [5] . Being closely related to diseases such as diabetes, fatty liver, hyperlipidemia, hypertension, cardiovascular diseases and metabolic syndrome, obesity also affects children's sleep and mental health, and seriously undermines children's normal growth and development [6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms remain to be elucidated, obesity-related hormonal changes including leptin and insulin resistance are speculated to contribute to early puberty [ 35 ]. It has been observed that obesity-related increases in circulating leptin activate hypothalamic Kiss 1 expression, which regulates GnRH pulse production and puberty onset [ 36 ]. Obesity-induced hyperinsulinemia was also shown to induce earlier pubertal onset by increasing androgen synthesis from the ovary and adrenal glands and by increasing the bioavailability of sex steroid hormones [ 35 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%